1992
DOI: 10.1164/ajrccm/145.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Lung-restricted Activation of the Alveolar Macrophage/Monocyte System in Pulmonary Sarcoidosis

Abstract: SUMMARY An activation of T-cells that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 15 publications
2
100
0
Order By: Relevance
“…Similar discrepancies exist between studies on cytokine production by sarcoid PBMNC. Some authors have found a decreased production of IL-1β, TNF-α and IL-6 by sarcoid PBMNC and have interpreted this as a consequence of the postulated "anergic state" [22][23][24][25]. Others have detected an enhanced IL-6 generation by sarcoid PBMNC [9,26], which would be in line with the view that these cells are activated [27].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar discrepancies exist between studies on cytokine production by sarcoid PBMNC. Some authors have found a decreased production of IL-1β, TNF-α and IL-6 by sarcoid PBMNC and have interpreted this as a consequence of the postulated "anergic state" [22][23][24][25]. Others have detected an enhanced IL-6 generation by sarcoid PBMNC [9,26], which would be in line with the view that these cells are activated [27].…”
Section: Discussionmentioning
confidence: 72%
“…In some of the studies that failed to detect enhanced cytokine production by sarcoid BALC, bioassays were used for supernatant analysis [19,22], allowing specific inhibitors to interfere with cytokine activity [21,24]. Another bias could result from differences in patient populations regarding disease severity and smoking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…These previous results indicated that sTNF-R may contribute to regulating TNF--mediated disease. Since TNFhas been suggested to play an important role in the pathogenesis of sarcoidosis [3][4][5][6], one might speculate that sTNF-R in sarcoidosis may contribute to the homeostatic regulation of granuloma formation. Therefore, in addition to estimating the levels of plasma sTNF-R, we also measured plasma TNF-levels and attempted to analyse the relationship between the ratio of plasma sTNF-R levels to plasma TNF-levels and the course of sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of sarcoidosis has been extensively investigated, and several inflammatory cells and cytokines play a crucial role in its pathogenesis [1][2][3]. Several studies of macrophage/monocyte-derived cytokines such as IL-1 and TNF-have demonstrated an increased production of these cytokines by unstimulated and stimulated macrophages/monocytes from patients with sarcoidosis [4][5][6]. In addition, the involvement of these cytokines in the formation of granulomata has been shown by employing experimental granulomata and dextran-induced granulomata [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar macrophages from sarcoidosis patients with active sarcoid secrete large amounts of TNF-␣ [67,68], so there is at least a logical basis for this treatment [69][70][71]. It is often combined with once weekly methotrexate 10 mg per m 2 to reduce antibody formation against infliximab.…”
Section: Treatment Of Sarcoidosis With Infliximabmentioning
confidence: 99%